2021
DOI: 10.1038/s41419-021-04015-w
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy-related circRNA evaluation reveals hsa_circ_0001747 as a potential favorable prognostic factor for biochemical recurrence in patients with prostate cancer

Abstract: Prostate cancer (PCa) is a common high-incidence malignancy in men, some of whom develop biochemical recurrence (BCR) in the advanced stage. However, there are currently no accurate prognostic indicators of BCR in PCa. The aim of our study was to identify an autophagy-related circular RNA prognostic factor of BCR for patients with PCa. In this study, immunochemistry revealed that the classic autophagy marker MAP1LC3B was positively correlated with Gleason score. Least absolute shrinkage and selector operator r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…Finally, the two subgroups were then compared to validate the predictive model, too. We constructed the nomogram and calibration plots based on our previous study ( Zhong et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the two subgroups were then compared to validate the predictive model, too. We constructed the nomogram and calibration plots based on our previous study ( Zhong et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transwell assay was conducted to examine the invasiveness of MAFG-AS1 downregulated cells. Detailed procedures of the above assays are available in our previous study ( Zhong et al, 2021 ). All experiments were implemented with three triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, clarifying the correlation of circRNAs and autophagy seems particularly important to the research about pancreatic cancer. In the study of autophagy-related circRNA, it has been found that there is an interactive regulatory relationship between circRNA and autophagy in non-small cell lung cancer [ 30 ], bladder cancer [ 31 ], and prostate cancer [ 32 ]. However, the regulatory relationship in pancreatic cancer is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of circRNAs has also assessed in PCa. For instance, expression levels of hsa_circ_0000437, hsa_circ_0000280, and circ_5017 have been correlated with poor survival of patients (97). Moreover, expression of circABCC4 has been associated with advanced clinicopathological features including higher tumor stage, metastasis and poor clinical outcomes (53).…”
Section: Diagnostic and Prognostic Applications Of Circrnas In Pcamentioning
confidence: 99%